Morphology of flux avalanches in patterned superconducting films - Zadorosny, R. [UNESP]; Colauto, F.; Motta, M.; Johansen, T. H.; Dinner, R.; Blamire, M.; Ataklti, G. W.; Moshchalkov, V. V.; Silhanek, A. V.; Ortiz, W. A. (Springer Nature, 2013)
It is well known that under certain circumstances, magnetic fields applied perpendicularly to the plane of superconducting films can trigger flux avalanches. In such cases, the penetration has a tree-like profile. However, in samples where a regular array of antidots, ADs, is present, the avalanches follow the rows of ADs as if they were guiding lines for the abrupt penetration. In this work, we used the magnetooptical imaging technique to study the morphology of flux avalanches in two Nb films with a square lattice of square ADs, each one with a different lateral size, and a plain film for reference. We show that the morphology of the flux avalanches is greatly influenced by the size of the interstitial region. © 2012 Springer Science+Business Media, LLC.
Keywords: Antidots; Flux avalanches; Magnetooptical imaging; Lateral sizes; Magneto-optical imaging techniques; Nb film; Regular array; Square lattices; Imaging techniques; Superconducting films; Morphology